Pencegahan Gelombang ke Tiga melalui Health Education Penguatan Disiplin Protokol Kesehatan COVID-19 Di Desa Margamukti Sumedang Utara - Heri Ridwan; Iis Aisyah; Ayu Prameswari Kusuma Astuti; Delli Yuliana Rahmat; Hikmat Pramajati (Universitas Mathla'ul Anwar Banten, 2022)
PREVENTION OF THE THIRD WAVE THROUGH HEALTH EDUCATION STRENGTHENING DISCIPLINE OF COVID-19 HEALTH PROTOCOLS. The mortality rate due to the COVID-19 pandemic in the world has increased to 3,893,114 people and as many as 179,657,832 were confirmed positive on June 24, 2021. In West Java Indonesia, the mortality rate has reached 4,826. In The, North Sumedang recorded 14 people died out of 662 confirmed positive cases until June 23, 2021. Meanwhile, in October 2021 the number of confirmed COVID-19 began to decrease, but the people began to lack discipline in implementing health protocols, fearing a third wave of COVID-19 would occur in Indonesia. The purpose of this community service was to increase public knowledge, awareness and obedience to the importance of implementing health protocols during the COVID-19 pandemic. The methods of lectures, discussions, evaluations and the practiced of implementing health protocols to prevent the spread of COVID-19 were used. The results after this activity showed that the majority of participants have Very Good knowledge and skills to implemented COVID-19 health protocols. We hope that people who have received these activities can disseminate, remind their families and surrounding people to implement and actively participate in health promotion regarding the discipline of implementing the COVID-19 health protocol.